2018
DOI: 10.3847/1538-3881/aaeff1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Spot Stability in the Post-common-envelope Binary QS Vir

Abstract: We observed the post-common-envelope eclipsing binary with a white dwarf component, QS Vir, using the 1.88 m telescope of Kotammia Observatory in Egypt. The new observations were analyzed together with all multicolor light curves available online (sampling a period of 25 years), using a full-feature binary system modeling software based on Roche geometry. This is the first time complete photometric modeling was done with most of these data. QS Vir is a detached system, with the red dwarf component underfilling… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…In the case of an eclipsing WDMS system, the depths of the eclipse observed in different bands vary and they are determined by the ratio of temperatures of the components. For a typical system, which consists of a late red dwarf and a WD, observed eclipse depths increase from IR to UV (Maxted et al 2004;Law et al 2012;Parsons et al 2013b;Latković et al 2019). However, in the case of GPX-TF16E-48, multi-colour photometric follow-up observations revealed that depths of eclipses show an unusual colour dependence with an excess in red filters (see Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the case of an eclipsing WDMS system, the depths of the eclipse observed in different bands vary and they are determined by the ratio of temperatures of the components. For a typical system, which consists of a late red dwarf and a WD, observed eclipse depths increase from IR to UV (Maxted et al 2004;Law et al 2012;Parsons et al 2013b;Latković et al 2019). However, in the case of GPX-TF16E-48, multi-colour photometric follow-up observations revealed that depths of eclipses show an unusual colour dependence with an excess in red filters (see Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Also, if only ellipsoidal variability was present, its depth around the orbital phase 0.0 would be smaller than that at the phase 0.5. These features indicate the presence of spot(s) on the surface of the MS star (Tappert et al 2007;Parsons et al 2016;Latković et al 2019).…”
Section: Light Curves Modellingmentioning
confidence: 94%
See 1 more Smart Citation
“…The hibernation scenario would require the existence of a large number of detached red dwarf/white dwarf binaries with a configuration close to Roche lobe filling of the secondary star. Up to now, there is only one such case observed, QS Vir (Latkovic et al, ), but according to the Gaia Collaboration et al (), this star is the second closest known CV‐like object (distance d = 50 pc), apart from WZ Sge ( d = 45 pc). Henry et al () analyzed the completeness of stars or stellar systems containing white dwarfs or red dwarfs in the solar neighborhood and concluded that a more or less complete census of such objects (70–90%) is only achieved for distances d = 10 pc, while for larger distances, many of those targets have escaped detection (implying that we presently know only ∼30% for d = 25 pc; ∼15% for d = 50 pc, which is the distance of the nearest CVs; and only ∼2% for d = 100 pc).…”
Section: Are the Modern Counterparts Of Ancient Classical Novae Too Fmentioning
confidence: 99%